An Analysis of Code Mixing in Indonesian Movie Cek Toko Sebelah - Muhammad Ricky Adrean; Bukhari Daud; Kismullah Kismullah (Universitas Syiah Kuala, 2020)
In using the language, people have a variety of style, one of them is code mixing. Indonesian-English code mixing often uses by teenagers because of influence of popular movie like Cek Toko Sebelah that contain code mixing. The teenagers who watched this movie may be exposed to every aspect presented in the movie, including language use along with code-mixing phenomenon in it. Thus, it is significant to investigate the use of code mixing in this movie. The aim of this study is to find out the types of code mixing that are used in Cek Toko Sebelah movie and also to figure out the type of code mixing that is most frequently used in Cek Toko Sebelah movie. This study used qualitative method. In collecting the data, the writer used observation sheet and classified the data into 3 types of code mixing based on Muysken’s (2000) theory. The result of this study showed that 32 data or (63%) are categorized as insertion, 19 data or (37%) are categorized as alternation and no data of congruent lexicalization. The most frequently used type of code mixing in Cek Toko Sebelah movie was insertion.